Inserção do bordado no segmento moda-vestuário no Ceará: uma análise institucional no campo da economia criativa - Souza, Ligia Carla de Lima (2015)
The changes in the macroeconomic scenario of the late twentieth and early twenty-first century pointed to creativity as a new economic force, responsible for the outbreak of a new field of study, known as the creative economy. Included in the scope of this "new economy", the fashion industry seems to gain a new concept in the creation and development of products such as creative sector. In the search for a competitive edge, the possibility of inserting the fashionable craft is the meeting of two different production languages which makes it possible to fashion be of symbolic and intangible values, representative of a Brazilian cultural identity at the same time enables up a path to economic sustainability of craftsmanship, represented in this research by embroidery type. In this sense, this work will address the integration of embroidery in fashion-clothing segment in the state of Ceará, through an analysis of the institutional environment formed by the actors present in the dynamics of the creative economy, which were listed following the structure of institutional arenas of business systems (The State, Financial System, Skill Development and Control System, Trust and Authority Relations), proposed by Whitley (1999). Therefore, we conducted a qualitative study of exploratory and descriptive, with the research strategy case study. Data collection was conducted through interviews with 22 representatives from 14 institutions. The data were analyzed using content analysis technique. As a result, the various actors had positive aspects about the viability of embroidery in the fashion industry in terms of market potential, cultural development, regional development, tourism favoritism and employment opportunity, however, its institutional actions denote an acting level unable to foster the integration of embroidery in fashion, converging to an unfavorable scenario. The results showed that the analyzed institutional environment has difficulty creating institutional capacity to strengthen the creative economy.